Correlation of morphological variants of soft palate and types of malocclusion: A digital lateral cephalometric study - Deepak Samdani; Anjali Saigal; Esha Garg (Wolters Kluwer Medknow Publications, 2015)
Aims and Objectives: The morphology of soft palate has variable presentations on lateral cephalometry. The aim of our study was to investigate the correlation between various shapes of soft palate and types of malocclusion in different gender groups among North Indian individuals. Materials and Methods: The study sample comprised randomly selected 250 healthy North Indian individuals (125 males and 125 females) seeking orthodontic treatment for malocclusion without any speech abnormality or any other syndromes or diseases and with age ranging from 14 to 28 years. Clinically, in all subjects, the type of malocclusion was examined and categorized according to Angle's classification of malocclusion. The morphological variants of soft palate were also assessed on digital lateral cephalogram and were allocated to one of the six patterns as described by You et al. The differences in the proportion of each type were studied and variation of malocclusion and soft palate morphology between gender groups was also assessed. The results obtained were subjected to a statistical analysis to find the correlation between variants of the soft palate and types of malocclusion in different gender groups. Results: In our study, the frequency of rat tail (37.2%) type of soft palate was seen in highest proportion, whereas the frequency of distorted S-shape (6.80%) was least in both the genders. Angle's class II malocclusion (51.2%) was the most common, followed by class I (43.2%), whereas class III (5.6%) was found to be the least prominent type in both the genders. Patients with Angle's class I malocclusion were most frequently found to have rat tail type soft palate, those with Angle's class II had leaf-shaped soft palate, and those with Angle's class III had crooked shaped soft palate. Angle's class II and class III malocclusions were significantly correlated with soft palate shapes, whereas Angle's class I malocclusion was highly significantly correlated with the shape of soft palate. Conclusion: It was found in our study that there was a significant correlation between variants of soft palate and types of malocclusion.